The Use of One-Way Multivariate Analysis of Variance in the Impact of the Database on the Fields of Banking Service in Some Iraqi Banks - هدو عادل احمد (Journal of Economics and Administrative Sciences, 2019)
The purpose of this paper is to recognize the impact of database levels on fields of banking service (provision of remittance services and transfer of funds, save financial deposits, provision of personal loans services) in some of Iraqi banks using one-way multivariate analysis of variance. The paper population consisted of (120) employees, then a random stratified sample of (104) employees was taken. A questionnaire paper consists of (24) items were designed in order to analyze by one-Way multivariate analysis of variance (MANOVA) using SPSS.One of the main findings of the current paper is that there is an impact of database on fields of banking service in Iraqi banks (Al Rafidain and Al Rasheed).